The Negotiation of Social Sanctions towards Karman in Ahmad Tohari’s Kubah - Ilham Awaliyah Pimay; Sukarjo Waluyo; M. Suryadi (SUAR BETANG, 2023)
This research examines the negotiation of social sanctions against the main character Karman in the novel Kubah by Ahmad Tohari. This research uses literary sociology theory with text analysis to identify the factors of the negotiation of social sanctions against former PKI sympathizers in the novel. The results show that (1) Pegaten Village community is thick with rural life and Javanese philosophy inherent in each individual; (2) Javanese philosophy described in the novel includes kamanungsan, tepa slira, sikap perwira, aja dumeh, manungaling kawula gusti, and budi luhur, (3) negotiation of social sanctions materialized in the novel due to Javanese cultural values in life adopted by the local community. Instead of punishing former PKI sympathizers, Pegaten villagers gave Karman the opportunity to make a mosque dome as a form of acceptance of one's dark past. AbstrakPenelitian ini mengkaji negosiasi atas sanksi sosial terhadap tokoh utama Karman dalam novel Kubah karya Ahmad Tohari. Penelitian ini menggunakan teori sosiologi sastra dengan analisis teks untuk mengidentifikasi faktor adanya negosiasi sanksi sosial terhadap eks simpatisan PKI dalam novel. Hasil penelitian menunjukkan bahwa (1) masyarakat Desa Pegaten kental akan kehidupan perdesaan dan falsafah Jawa yang melekat dalam diri tiap individu; (2) falsafah Jawa yang digambarkan dalam novel Kubah meliputi kamanungsan, tepa slira, sikap perwira, aja dumeh, manungaling kawula gusti dan budi luhur, (3) negosiasi atas sanksi sosial terwujud dalam novel Kubah disebabkan oleh nilai-nilai kebudayaan Jawa dalam berkehidupan yang dianut oleh masyarakat setempat. Alih-alih menghukum eks simpatisan PKI, masyarakat desa Pegaten justru memberi Karman kesempatan untuk membuat kubah masjid sebagai wujud penerimaan atas masa lalu seseorang yang kelam.